Variações temporais no grau de glicemia e condição corporal de Artibeus planirostris em áreas de tabuleiro e mata atlântica no estado da Paraíba - Ximenes, Monique Silva (2013)
Variations in the Body Condition Index (BCI), glycemia and ketonemia of Artibeus planirostris (Chiroptera: Phyllostomidae) were analyzed in Tabuleiro and Atlantic Forest areas of Paraíba State, at field and captivity conditions. BCI was chosen based on the minimum influence of forearm length on body mass and evaluated according to sex, reproductive status, location and time of capture. Glycemia and ketonemia were also correlated with BCI and other variables. Variations in the BCI and glycemia were recorded after capture, fasting and feeding bats in captivity. The results showed that Le Cren’s Relative Condition Factor (Kn) and Simple Ratio with Curve Fitting (CFt) indices were the most suitable for A. planirostris. Blood glucose was correlated with Kn and proved to be a good method to validate the BCI. In Guaribas Biological Reserve, females had higher Kn, probably related to biases in the methodology or energy reserves during reproductive status. Tabuleiro’s bats had higher Kn and glucose levels than those in Atlantic Forest, which may indicate sub-sampling by the exclusion of bats in the canopy of the latter area. The twelve hours of collection indicated that A. planirostris forages throughout the night and presents a variation of Kn and glucose, especially during early morning, when it reaches the maximum levels before it returns to the shelter. In captivity, bats showed a great variation of Kn and glucose levels after fasting and feeding, recording Kn measures for these states that can be used as a parameter for field studies in the region. Blood glucose remained at normal values for mammals, but about 30% of the bats had levels higher than normal during capture in all areas, probably due to stress. Ketone bodies have been correlated only to glucose, and thus were not considered a good method to validate Kn in these animals.